Crime, security and surveillance: effects for the surveillant and the surveilled - Vande Walle, Gudrun; Herrewegen, Evelien van; Zurawski, Nils; Van den Herrewegen, Evelien (Het groene gras, 2012)
Beyond criminal law : on the Dutch anti-social behaviour agenda -- Surveillance in the supermarket : technology and the pluralisation of crime control -- 'Better safe than sorry, but you know, don't overdo it' : responsibilisation and fatalism in perception of safety -- Citizen journalism, surveillance and control -- The nodal-network fallacy in the surveillance of transit migration in Belgian harbours -- Policing flows and nodes : a Dutch interpretation -- Securing the legitimacy of surveillance : automatic number plate recognition in Dutch policing -- The political geography of public space : on criminalisation and punishment, privatisation, dispersion and exclusion -- Police and surveillance in Paris : are the French police becoming knowledge workers and risk managers? -- Multiple views of DNA surveillance : the surveilled, the surveillants and the academics -- The boss as big brother : moral aspects of workplace surveillance -- The securitisation of environmental conflicts, a blessing or a curse?